Unveiling trends – healthcare-associated infections and prevention strategies in a tertiary care teaching hospital: a 5-year prospective surveillance study - Fomda, Bashir; Qadri, Uksim; Bashir, Gulnaz; Shah, Akbar; Baqal, Sehrish; Mir, Abdul Waheed; Nazir, Shaista; Wani, Saleem Javaid; Aman, Munaza (International Journal of Infection Control, 2026)
Background: Healthcare-associated infections (HAIs) pose a major threat to critically ill intensive care unit (ICU) patients. Limited data on HAIs in Indian ICUs necessitated this study at a tertiary care hospital in North India. Objective: To determine the incidence, distribution, and causative agents of HAIs, assess their antibiotic susceptibility profile, and evaluate the impact of infection prevention and control (IPC) measures. Design: This prospective study was conducted in the ICU settings of a tertiary care centre. Bloodstream infections (BSIs), central line-associated bloodstream infections (CLABSIs), urinary tract infections (UTIs), and catheter-associated urinary tract infections (CAUTIs) were defined according to standard definitions. The incidence and device utilisation ratio (DUR) were calculated. Identification and susceptibility were determined via BacT Alert and VITEK-2 Compact System. IPC compliance, including hand hygiene and central line insertion practices (CLIP), was monitored as per checklist. Results: Overall BSI rates of 12.85 per 1,000 patient-days, CLABSI at 22.11 per 1,000 central line-days, and CAUTI at 1.77 per 1,000 urinary catheter-days were recorded. The DUR was calculated to be 0.44 and 0.6 for CLABSI and CAUTI respectively. Burkholderia cepacia (52.8%) was the predominant CLABSI pathogen, while Acinetobacter spp. (22.2%) was the most common CAUTI pathogen. Hand hygiene compliance improved from 40% in 2019 to 70% in 2023, CLIP adherence increased from 30 to 75%, CLABSI and CAUTI rate reduced from 19.66 to 8.59 and 8.66 to 0.75, respectively. Conclusion: The study highlights the need for stringent IPC measures, robust antibiotic stewardship, and continuous surveillance to mitigate HAIs.